Pengaruh Biaya Operasional Terhadap Laba Bersih PT. Sari Indah Teguh Purwakarta Periode 2013 – 2017 - Gunardi Gunardi; Sugianto Ikhsan; Syafirah Sehaq (Accounthink, 2019)
The main objective of the research is to find out the influence of operating cost to net profit PT. Sari Indah Teguh Purwakarta of period 2013 - 2017. The method used was a quantitative. The data collection by observation, and literature study. The technique used to analize the date were the normality test, coefficient of correlation, coefficient of determination and linier regeression analysis. The obtained data showed that the data was normally distributed. The correlation result 0,936. The coefficient of determination result is 0,876 it means that net profit can be influenced by operating cost 87,6 %. Linier Regression analysis result is Y=1775.963 + (0.722)X. The problems is: the lacks of minimized operational cost, and the recent price of gas. The suggestions: Reviewing operational costs in further detail, Controlling the usage of electricity, water, and office stationary.